Effects of dietary guar gum with different viscosity on growth performance and intestinal health in pearl gentian grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Zhu, Lulu; Chi, Shuyan; Zhang, Shuang; Xie, Shiwei; Tan, Beiping; Deng, Junming (Frontiers in Marine Science, 2025)
The study aimed to evaluate the impact of guar gum (GG) with different viscosity on growth rate and gut health of pearl gentian grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂). Juvenile groupers (6.66 ± 0.08 g) were reared for 10 weeks and fed four different diets: three containing 8% GG with low, medium, and high viscosity (designated as GGL, GGM, and GGH, respectively), and a control diet, in which 8% GG was replaced with 8% cellulose. The results indicated that at an 8% inclusion level, all three viscosities of GG significantly reduced both growth rate and feed utilization, with the lowest values observed in the GGH group. Similarly, dietary inclusion of GG with various viscosity decreased the intestinal activities of lipase, alkaline phosphatase and lysozyme as well as the content of immunoglobulin M, increased the plasma diamine oxidase activity and endothelin-1 level. Additionally, dietary GG inclusion regardless of viscosity up-regulated the relative expressions of intestinal proinflammatory cytokines, while down-regulated the relative expressions of intestinal anti-inflammatory cytokines and tight junction proteins. Notably, dietary inclusion of 8% GGH decreased intestinal villus length and total antioxidant capacity but increased intestinal malondialdehyde and secretory immunoglobulin T contents. Dietary GG supplementation reduced the α-diversity of the intestinal microbiota and decreased the relative abundance of Proteobacteria and Firmicutes, while increasing the relative abundance of Fusobacteriota, particularly Cetobacterium. This shift in microbial composition was associated with decreased levels of acetic and valeric acids but increased levels of caproic and isovaleric acids. These findings indicated that when using GG as a feed binder, it is important to consider its viscosity, as excessively high viscosity may negatively impact growth rate and intestinal health.